Propaganda Chimera: Unpacking the Iranian Perception Information Operations in the Arab World - Elswah Mona (De Gruyter, 2021)
In the past four years, Iranian Information Operations (IOs) have received a lot of scrutiny by social media companies and policymakers. From 2018 to 2021, several accounts on Twitter, Facebook, and Instagram were taken down by tech companies for engaging in coordinated inauthentic behaviour. Despite the heated relationship between Iran and many Arab countries, the Iranian IOs in the Arabic online sphere have received less academic attention over the years. This study fills this gap by being one of the few studies to investigate the Iranian IOs in the Arab world. We analyse more than 9.3 million tweets posted from 2008 to 2020 using the hashed datasets shared by Twitter’s Election Integrity Hub. We found that Iran’s IOs have made the Arab world its primary target—despite the attention the US claims to receive from them. However, these IOs demonstrate very little engagement and reach amongst Arab users, limiting the possibilities of Iran infiltrating the online Arabic sphere, and fostering weak yet unruly Arab counterpublics. This study argues that Iran’s IOs garner their power from being perceived as efficient and dangerous operations that could pollute the public sphere of overseas nations, rather than through actual infiltration through engagement. We understand Iran’s efforts to be preoccupied with old propaganda efforts, through their investment in websites and imitation of news organisations. However, their efforts prove that Iran adopted the tactics of “new propaganda” that depend on creating a perceived atmosphere of distrust and chaos. We contribute to the discussion on information operations by proposing the term “perception IOs”, referring to IOs by governments that aspire to be perceived as effective meddling countries in foreign politics.